Xenophobic attacks, migration intentions and networks: Evidence from the South of Africa - Guido Friebel; Juan Miguel Gallego; Mariapia Mendola (Institute for the Study of Labor (IZA), 2011)
We investigate how emigration flows from a developing region are affected by xenophobic violence at destination. Our empirical analysis is based on a unique survey among more than 1000 households, collected in Mozambique in summer 2008, a few months after a series of xenophobic attacks in South Africa killed dozens and displaced thousands of immigrants from neighbouring countries. We estimate migration intentions of Mozambicans before and after the attacks, controlling for the characteristics of households and previous migration behaviour. Using a placebo period, we show that other things equal, the migration intention of household heads decreases from 37% to 33%. The sensitivity of migration intentions to violence is larger for household heads with many children younger than 15 years, decreasing the migration intention by 11% points. Most importantly, the sensitivity of migration intentions is highest for those household heads with many young children whose families have no access to social networks. For these household heads, the intention falls by 15% points. Social networks provide insurance against the consequences young children suffer in case the household head would be harmed by xenophobic violence and consequently could not provide for the family.
urn:nbn:de:101:1-20110927245
Keywords: O1; R2; J6; D1; 330; violence; risk; household behaviour; Mozambique